Inhibition of the integrated stress response reverses oxidative stress damage-induced postoperative cognitive dysfunction - Jiang, Linhao; Dong, Rui; Xu, Minhui; Liu, Yujia; Xu, Jiyan; Ma, Zhengliang; Xia, Tianjiao; Gu, Xiaoping (Frontiers in Cellular Neuroscience, 2022)
Postoperative cognitive dysfunction (POCD) is a common complication following anesthesia and surgery that might lead to a decline in learning and memory. Oxidative stress damage is one of the pathogenic mechanisms underlying POCD. Recent studies had shown that the integrated stress response (ISR) is closely related to oxidative stress. The core response of ISR is phosphorylation of eIF2α.Various cellular stress stimuli trigger activation of eIF2α kinases, thus causing phosphorylation of eIF2α. ISR is associated with many neurodegenerative diseases; however, the relationship between POCD and ISR has not been defined. In the present study the tibias in 4-month-old C57BL/6 mice were fractured under isoflurane anesthesia to establish the POCD animal model. Cognitive function was assessed by fear conditioning tests and the Y-maze from 3-14 days post-surgery. Western blot was used to determine the levels of P-eIF2α, eIF2α, ATF4, GADD34, CHOP, BDNF, proBDNF, and p-NR2B expression. The levels of reactive oxygen species (ROS), superoxide dismutase (SOD), and malondialdehyde (MDA) were measured to determine oxidative stress in hippocampal tissues. After tibial fracture surgery in mice, the hippocampus had increased levels of P-eIF2α, ATF4, GADD34, and CHOP protein, ROS-positive cells, and average fluorescence intensity, SOD activity was decreased, and the MDA level was increased. The ISR inhibitor, ISRIB, reduced the levels of P-eIF2α, ATF4, GADD34, and CHOP protein, and alleviated oxidative stress in the hippocampus of POCD mice. Moreover, ISRIB ameliorated cognitive dysfunction in POCD mice. Our findings suggested that targeting ISR may represent an effective approach to combat POCD.